1963
DOI: 10.1152/ajplegacy.1963.205.6.1099
|View full text |Cite
|
Sign up to set email alerts
|

Separation of pepsin I, pepsin II A, pepsin II B, and pepsin III from human gastric mucosa

Abstract: Extracts of human gastric mucosa have been fractionated on diethylaminoethyl cellulose to yield three precursors of proteolytic enzymes active at low pH which have been called pepsinogen I, pepsinogen II, and pepsinogen III. Pepsinogen I has been found in the mucosa from all parts of the stomach examined as well as in the proximal duodenum. Pepsinogen II and pepsinogen III were present in fundic mucosa only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1

Year Published

1970
1970
1986
1986

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(9 citation statements)
references
References 0 publications
0
8
1
Order By: Relevance
“…No difference in heat inactivation was observed between PI and PII. These findings differ from the results of Seijffers et al who found their pepsin I (PII) more heat-resistant than other pepsins [14].…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…No difference in heat inactivation was observed between PI and PII. These findings differ from the results of Seijffers et al who found their pepsin I (PII) more heat-resistant than other pepsins [14].…”
Section: Discussioncontrasting
confidence: 93%
“…During alkali activation PII proved to be more stable than porc pepsin and PI. These differences in stability have already been observed and used for the separate enzymatic determination of those pepsins [14,15]. No difference in heat inactivation was observed between PI and PII.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Human gastric juice contains several pepsins [9] and there is some evidence to suggest that pepsin I may be the most important of these in the peptic ulcer diathesis [10,13]. On the other hand, it must be pointed out that the various authorities use widely varying methods of measuring the pepsin I fraction and that there is no international agreement as to its identity.…”
Section: Discussionmentioning
confidence: 99%
“…One unit of activity was defined as the amount which caused an increase of 1 Aase/min under the above conditions. Milk clotting activity was measured as in [7] . Protein was determined as in [8] using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%